Prinsip Muamalah dalam Ekonomi Syariah: Tinjauan dan Implementasi - Rodia Rotani Rianda; Bella Anggraini; Sarah Dalila Fitri; Wismanto Wismanto (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
This journal discusses the principles of muamalah in the context of sharia economics, with the aim of understanding how these values ​​are implemented in daily practice. This research uses a qualitative approach with interviews and literature study as the main methods. The research results show that sharia-compliant muamalah not only contributes to economic sustainability, but also improves social justice. It is hoped that this article will provide insight for economic actors and academics in understanding and applying the muamalah principle.